2011
DOI: 10.1007/s12402-011-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking in adults with ADHD

Abstract: Adults with ADHD have problems in everyday multitasking situations presumably because of deficits in executive functions. The present study aims to find out (a) whether adults with ADHD show deficient multitasking performance in a standardized task, (b) how they perceive the multitasking situation, and (c) which task structure might be beneficial for them as compared with adults without ADHD. Therefore, we experimentally compared task performance, mood, and motivation in a group of 45 men with ADHD (M-age = 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…Regarding subjective ratings of mood, the ADHD patients reported more ADHD symptoms, depression, and anxiety, as well as more negative and less positive affect compared with healthy controls, as expected [ 24 , 25 ]. MAP improved these symptoms in the ADHD patients, in accordance with the results of Mitchell et al [ 43 ] and Zylowska et al [ 15 ], and in the healthy controls, as reported by Astin [ 9 ], Jha et al [ 10 ], and van den Hurk et al [ 11 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Regarding subjective ratings of mood, the ADHD patients reported more ADHD symptoms, depression, and anxiety, as well as more negative and less positive affect compared with healthy controls, as expected [ 24 , 25 ]. MAP improved these symptoms in the ADHD patients, in accordance with the results of Mitchell et al [ 43 ] and Zylowska et al [ 15 ], and in the healthy controls, as reported by Astin [ 9 ], Jha et al [ 10 ], and van den Hurk et al [ 11 ].…”
Section: Discussionsupporting
confidence: 74%
“…Regarding affect, ADHD is associated with a lower quality of life [ 21 – 23 ], decreased mood and arousal, and low motivation, all of which can be associated with impaired attentional performance [ 24 , 25 ] because they relate to cognitive control (conflict resolution, planning, inhibitory control, and error correction) and emotional regulation [ 26 ]. In this context, MAP could improve the cognitive/affective processes [ 6 , 27 , 28 ] that are impaired in adults with ADHD [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It might be that due to experience and practice, they learned to cope with media distractions in their day-to-day lives. For example, Gawrilow et al (2011) showed that adults with and without ADHD did not differ in their performance in a laboratory multitasking task but that adults with ADHD underestimated their performance and felt more stressed when exposed to the task. Moreover, adults with ADHD showed the best performance and mood in a well-structured task in comparison to the unstructured multitasking situation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, even in situations that require sustained attention for longer periods of time, they may be aware of their urge to lose attention and may compensate this with extra effort. Thus, due to socialization and development, adults with attention problems may have learned to control their attention more efficiently than children with attention problems (Faraone et al, 2006;Gawrilow, Merkt, Goossens-Merkt, Bodenburg, & Wendt, 2011). In the context of media multitasking, this may indicate that children with attention problems may be more easily distracted by other media activities than adults with these same problems.…”
Section: Interaction Effects Between Age and Attention Problems On Comentioning
confidence: 99%
“…Furthermore, the same group narrowed this effect down specifically to deficits in long-term planning rather than the recall of planned action, plan integrity, or self-initiation. Support for difficulties in long-term planning functions also comes from a number of sources including in relation to goal setting (Nyman et al, 2010), 'if-then' plans (Gawrilow, Merkt, Goossens-Merkt, Bodenburg, & Wendt, 2011) and planning scripts (Desjardins, Scherzer, Braun, Godbout, & Poissant, 2010). Prospective memory, especially time-, as opposed to eventbased memory, also appears to be impaired in ADHD (Talbot & Kerns, 2014).…”
Section: Reinforcementmentioning
confidence: 99%